The population of Jernang rattan (Daemonorops draco) in Jebak Village, Batanghari District, Jambi Province, Indonesia - IIK SRI SULASMI; NISYAWATI NISYAWATI; YOHANES PURWANTO; SITI FATIMAH (Society for Indonesian Biodiversity, 2012)
Sulasmi IS, Nisyawati, Purwanto Y, Fatimah S. 2012. The population of Jernang rattan (Daemonorops draco) in Jebak Village, Batanghari District, Jambi Province, Indonesia. Biodiversitas 13: 205-213. Research of Rattan Jernang ((Daemonorops draco Willd.) population in Jebak Village, Batanghari District, Jambi had never been done before. Daemonorops draco is a plant that produces sap called dragon blood. Dragon blood is very useful for the the lives of people of Anak Dalam Tribe in Jambi. This research used purposive random sampling method. All of data were analyzed descriptively. The results showed that beside D. draco, there were other six species of rattan in Jebak forest. The population of D. draco in Jebak forest was only 8 clumps, consisting of 82 individuals. D. draco had the smallest population among all rattan species. Calamus javensis had the highest population, namely 11 clumps, consisting of 197 individuals. The research location had air temperature of 20.2 oC-28.9 oC, relative humidity of 58%-68%, and pH of 4.60-4.81. In this location, there were 35 tree species (73 individuals) as supporting trees for D. draco to climb. The number of D. draco’s supporting trees and D. draco was not balanced, causing the death of D. draco in Jebak forest. Vegetation analyses showed that there were 51 tree species with diameter > 10 cm, consisting of 69 individuals. Pithecolobium saman had the highest importance value index (11) among all trees. There were also 33 tree species with diameter < 10 cm, consisting of 60 individuals. Pithecolobium saman also had the highest importance value index (20) in this group. Based on the interview, it is showed that the population of D. draco in Jebak forest declined because of illegal logging and forest encroachment.